Screening for Developmental Language Disorder in Bilingual Children Using an Iconic Gesture Comprehension Task. - Van den Eynde, Lotte; Zink, Inge; Vandermosten, Maaike; Romboutsa, Ellen (Language, Speech & Hearing Services in Schools, 2026)
Background: Traditional language assessments using monolingual standardized tests often lead to misdiagnoses in bilingual children due to variations in language experiences. Given the strong link between iconic gestures and language abilities, an iconic gesture comprehension task could serve as an effective screening tool for bilingual children with developmental language disorder (biDLD), as it does not necessitate verbal output. Therefore, we explored the potential and validity of such a screening tool. Method: We developed an iconic gesture comprehension task where children observe a gesture and select the corresponding image from four options. The task was completed by 70 monolingual children with typical development (moTD), 70 bilingual children with typical development (biTD), and 40 biDLD between 3 and 9 years old. Additionally, language tests were administered to gain insight into the relation between gesture performance and language abilities. Results: Performance on the gesture task increased with age, and group comparisons revealed that moTD and biTD outperformed biDLD. Although the task was unaffected by language experience, diagnostic accuracy at the individual level was 68.18%. Additionally, gesture performance was associated with lexicosemantic abilities in biDLD, suggesting that the task appears most sensitive to children with significant semantic deficits. Conclusions: While the iconic gesture comprehension task differentiated between children with and without developmental language disorder at the group level, its diagnostic accuracy at the individual level remains limited. Further research is needed to assess whether the task, in a modified form, still has potential as a screening task and to clarify how gesture comprehension relates to language abilities.